Creazione, sviluppo e diffusione della conoscenza a sostegno dello sviluppo locale. Il caso Galydhà - Cabiddu, Francesca; Pettinao, Daniela (Piccola Impresa / Small Business, 2011)
Although recent literature has focused on the importance of knowledge in local development, there is not yet a precise theoretical formulation regarding the possibility, especially for territories characterised by a strong level of inertia, of reactivating the spiral of knowledge through the internalization of external knowledge. This paper has two aims: to bridge the above mentioned gap, and to put into practice such theoretical framework regarding the reactivation of the spiral of knowledge both in an area characterised by inertia, and in the companies that operate in such territory. Within the chosen territory, we have focused our attention on one company, Galydhà, specialised in the production of goat milk dairies. The adopted framework allows to determine the main processes which favour the overcoming of territorial inertia, by using external knowledge in order to improve tacit, historical and cultural knowledge.